Intra-household resource shares under poverty transfers: Evidence from Ecuador - José L. Casco (Banco de México, 2022)
This paper estimates a structural model of household behavior in the presence of cash transfers to recover the amount of resources allocated to men, women, and children. Using data from Ecuador, I find that there are important intra-household inequalities, but the transfer induces a redistribution of resources among household members. I further explore the potential implications of this reallocation of resources in several domains and find that transfers increase the women's control of resources and increase household welfare by reducing poverty, especially for women and children. I also show that when the mother controls the majority of the household resources, it affects the patterns of consumption of the household and how households react to unexpected shocks. These results contribute to understanding better the redistributive effects of income support programs.
Keywords: D13; I38; J22; O12; 330; Resource shares; Transfers; Control of resources; Poverty; Consumption